2010
DOI: 10.1002/tie.20373
|View full text |Cite
|
Sign up to set email alerts
|

Financing the global supply chain: Growing need for management action

Abstract: This article investigates a growing desire by companies to better manage the financing of the global Management Action supply chain and explores best practices. Supply‐chain managers and finance or treasury managers, however, live in different worlds, and integration does not come easily. The article argues that decentralized finance functions lead to financial inefficiencies. The authors identify five subarchitectures to competitive supply chains and argue that visualizing the supply chain financially is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Several years later, according to [8] Gupta and Dutta (2011), with increasingly fierce competition, it becomes more important to improve the efficiency of working capital by using cash that is trapped in the financial supply chain (FSC). Mathis and Cavinato (2010) [9] argued that banks should play a more active role in the FSC to integrate the resources in the chain. Silvestro and Lustrato (2014) [10] showed that banks are key players that can offer alternative supply chain solutions in the FSC.…”
Section: Definition Of Supply Chain Financementioning
confidence: 99%
See 1 more Smart Citation
“…Several years later, according to [8] Gupta and Dutta (2011), with increasingly fierce competition, it becomes more important to improve the efficiency of working capital by using cash that is trapped in the financial supply chain (FSC). Mathis and Cavinato (2010) [9] argued that banks should play a more active role in the FSC to integrate the resources in the chain. Silvestro and Lustrato (2014) [10] showed that banks are key players that can offer alternative supply chain solutions in the FSC.…”
Section: Definition Of Supply Chain Financementioning
confidence: 99%
“…Arbitrary means that mathematical optimization for determining the weights was not used as it would have required a mathematical model to have been imposed on the structure of the model. Absolutely more important (8,9,10) (1/10, 1/9, 1/8) 2, 4,6,8…”
Section: Fuzzy Analytical Hierarchy Process (Fahp) Frameworkmentioning
confidence: 99%
“…Such as financing and payments between large buyers and suppliers' conditions improve. The challenge banks and third-party service providers face the various needs of different customers from different industries.According to Wang (2016), supply chain finance (SCF) is based on its under remaining of the supply chain transaction structure and subtle elements of the exchange, through the control of a genuine material stream, business stream, data stream and capital stream with the center of the inventory network, gives liquidity to providers by utilizing their purchaser's higher credit rating to achieve value-added process.John Mathis and Cavinato (2010) findings show that many companies increasingly eager to explore the best practices in the management of global supply chain financing. Article refers to decentralized financial decisions resulted in low efficiency financing.…”
Section: -The Origination Of Supply Chain Financementioning
confidence: 99%
“…In order to integration the flow of physical goods and information, buyers and suppliers have to put the pressure on their banks to play a more proactive role in improving physical/financial supply chain (P/FSC) integration (Mathis and Cavinato 2010). Silvestro and Lustrato (2014) argued that financial institutions, usually banks, were key players in the economic activities of all supply networks in their capacity to provide alternate supply chain financing solutions.…”
Section: Scf Definitionmentioning
confidence: 99%